TRANSFORMING LANGUAGE LEARNING INTO PUBLIC VALUE, DIGITAL ENTREPRENEURSHIP, AND CREATIVE ECONOMY ECOSYSTEMS IN INDONESIA - Zalzulifa Zalzulifa; Muhamad Ridwan; Rabenir; Adrian Rodgers (Politeknik Negeri Media Kreatif, 2026)
This study introduces a novelty of pedagogical theory that extends conventional Project-Based LanguageLearning by integrating public exposure, entrepreneurial transformation, and creative economy ecosystemformation into language education. While existing language learning models largely treat project outputs asterminal academic products, PBLL reconceptualizes student learning outputs as potentially transformativepublic assets capable of generating social, cultural, and economic value. Using evidence drawn from One Day Digipreneur Expo 2026 involving 121 multidisciplinary students atUniversitas Pramita Indonesia, this study develops and empirically illustrates PBLL through a theory-buildingapproach supported by mixed-method case analysis. Findings suggest PBLL operates through fiveinterconnected dimensions: linguistic production, public validation, digital entrepreneurship activation,identity-based creative capitalization, and ecosystem transformation.The study proposes PBLL as a new theoretical contribution to language education, higher education innovation,and entrepreneurial pedagogy, while introducing the PBLL Transformative Cycle Model and Expo-BasedAcademic Commercialization (EBAC) as derivative conceptual contributions.This article contributes a new pedagogical theory for transforming language learning from classroom-boundpractice into socio-economic innovation ecosystems.